Selfcare Management and Strategies of Drug Development for COVID 19 - Sanjana Gaikwad1 , Swati Gaikwad1 , Mayuri Deshmukh1 , Jagdish Nikose1 , Ravi Kalsait 1, Praful Pati (Indian Journal of Forensic Medicine & Toxicology, 2020)
Corona virus disease (COVID 19) is a recently discovered pandemic. Coronavirus infectious diseaseoriginate from Wuhan, China and widely and quickly spread throughout the world. WHO pronounced it asPandemic. As the spread of disease is through contact and the rigidity of virus in term of its lifespan outsidethe human body its threat human beings is alarming with no thearapy to treat. As per the WHO guidelines theonly way to control is to prevent the disease by following selfcare method. Though the Scientific communitystarted research on the vaccine as well as newer drugs the development of which may require certain timeto reach at the people at large. Thus selfcare management is found to be the only strategy to combat theinfection by COVID 19.